Friction characteristics of amorphous carbon coating against various 3d-transition metals - Kim, Jae-Il; Lee, Woo-Young; Tokoroyama, Takayuki; Murashima, Motoyuki; Umehara, Noritsugu (Tribology international, 2022)
DLC has anti-friction characteristics due to the tribofilm formed by the carbon transfer to its mating material. However, its coefficient of friction depends on each mating material. This study aims to investigate a suitable mating material against diamond-like carbon coatings. We selected four 3d-transition metals (Ti, Fe, Ni and Cu) as the mating materials based on the chemical affinities for carbon, i.e., carbide formability and work of separation. Among them, Ti had the lowest coefficient of friction, followed by Fe, Ni and Cu. The structures of tribofilm formed on mating materials were characterized non-destructively using Raman spectroscopy consisting of confocal optics. It revealed that Ti could strongly attract the carbon and stably formed carbon-containing tribofilm, leading to low friction.